Fallet med den muterade science fictiondeckaren: Om populärkulturens litteraritet och didaktiska potential - Mehrstam, Christian (Tidskrift för litteraturvetenskap, 2010)
The Case of the Mutant Science Fiction Detective Story: Literariness and Popular Culture in Education This article states that the main schools of pedagogy of literature are in their respective ways designed to seize upon the benefits of literariness, which is a feature that some texts are still considered to have and others are considered to lack. With the example of Henrik Örnebring’s novel Blodsmak: Ett fall för Sennja Maler (»Taste of Blood: A Case for Sennja Maler«), it is demonstrated how a book that by all reader accounts lacks literariness, can be given it by altering the reader’s expectations. It is suggested that a turn in perspectives might be beneficial: the pedagogy of literature should be considered a creative activity, in the sense that it produces texts with desirable qualities rather than discovers »existent« qualities. This would open up a range of possibilities, for instance by making genre fiction more interesting to the education system. It is contended that this turn in perspectives could be strongly supported by modern systems theory, which would also bring wider implications for comparative literature.